2010
DOI: 10.1002/ejoc.201000188
|View full text |Cite
|
Sign up to set email alerts
|

Application of Halide Molten Salts as Novel Reaction Media for O‐Glycosidic Bond Formation

Abstract: Bond Formation. -Molten halide are used as novel reaction media for Koenigs--Knorr-type O-glycosidation reactions between glycosyl bromides and various phenolic acceptors. The high β-stereoselectivity, commercial availability of the glycosyl bromide and the ability to recycle the molten salt are features of this reaction. -(KUMAR, V.; TALISMAN, I. J.; MALHOTRA*, S. V.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…d, J =3.3 Hz, 1 H, H‐4), 5.15 (d, J =7.9 Hz, 1 H, H‐1), 5.12 (dd, J =10.4, 3.3 Hz, 1 H, H‐3), 4.22–4.09 (m, 3 H, H‐6a, H‐6b, H‐5), 2.17 (s, 3 H, Ac), 2.05 (s, 6 H, Ac), 2.00 ppm (s, 3 H, Ac); HRMS (ESI): calcd for C 20 H 23 NNaO 12 [ M +Na] + : 492.1112, found: 492.1112. The results show good accord with the reported data …”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…d, J =3.3 Hz, 1 H, H‐4), 5.15 (d, J =7.9 Hz, 1 H, H‐1), 5.12 (dd, J =10.4, 3.3 Hz, 1 H, H‐3), 4.22–4.09 (m, 3 H, H‐6a, H‐6b, H‐5), 2.17 (s, 3 H, Ac), 2.05 (s, 6 H, Ac), 2.00 ppm (s, 3 H, Ac); HRMS (ESI): calcd for C 20 H 23 NNaO 12 [ M +Na] + : 492.1112, found: 492.1112. The results show good accord with the reported data …”
Section: Methodssupporting
confidence: 92%
“…After bromination procedures, TBAHS (1.74 g, 5.12 mmol), 4-nitrophenol (0.93 g, 6.66 mmol), and then 8mL1m NaOH(aq) were added to the glycosyl bromide dissolved in 25 mL show good accord with the reported data. [52] According to protocol B,t he previous intermediate (1.17 g, 2.50 mmol) was dissolved in methanol (20 mL), then 10 %P d/C (100 mg) was added for hydrogenation. After the hydrogenation procedure in protocol Bh ad been performed, the filtrate was concentrated and purified by silica gel chromatography (EtOAc/hex-anes = 1:3t o1 :1) to provide compound 13 g (0.96 g, 87 % [53] O-(5-Aminonaphthyl)-2,3,4,6-tetra-O-acetyl-b-d-galactopyranoside (13h) According to protocol A,p enta-O-acetyl galactopyranoside 11 (2.0 g, 5.13 mmol) was dissolved in 33 %H Br in acetic acid (4 mL) for bromination.…”
Section: Galactose Derivative Synthesismentioning
confidence: 99%
“…However, the present century saw the emergence of room‐temperature ionic liquids (RTILs), which came as a ready solution for all of the constraints. Malhotra and co‐workers implemented a series of RTILs and molten halide salts for the glycosylation of acetabromo‐ α ‐ d ‐galactose with p‐ nitrophenol. By virtue of their unique ionic combination and their probable role in the glycosylation pathway, ILs holds the promise of being an extensively used solvent and activator in the future.…”
Section: Glycosylationsmentioning
confidence: 99%
“…We recently demonstrated that halide molten salts were effective media for O-glycosidation of phenols at elevated temperatures under ambient conditions. 31 This methodology was extended for use in room temperature ILs (RTILs), where in situ generation of silver carbene complexes in ILs promoted O-glycosidation of a variety of acceptors. The advantages of ILs as PTCs and our interest in developing aromatic O-glycosides for the treatment of cancer motivated us to examine phase transfer catalyzed glycosidation using a variety of ILs.…”
Section: Introductionmentioning
confidence: 99%